1977
DOI: 10.1073/pnas.74.3.1013
|View full text |Cite
|
Sign up to set email alerts
|

Ionic regulation in genetic translation systems.

Abstract: The polyelectrolyte theory can provide an interpretation of the interdependence of pH, ionic strength, and polyamines one observes in the activity of ribonuclease acting on RNA. According to this theory:(i) A nucleic acid-enzyme complex and the suspending medium may be considered as two phases in equilibrium, even though within limits, the complex is soluble in water.(ii) The enzymatic catalysis is under tight control of the electrostatic potential generated by the system. Consequently, modification in electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Fig.8 shows that lowering the pH raised the K" optimum of the 30-S-coupled EF-G GTPase reaction. This suggests [24] that negative charges, probably from ribosomal RNA, are exposed in the vicinity of the catalytic center, upon interaction between the ribosomal subunits.…”
Section: Modulation By P H Of Ef-g Gtpase Activitymentioning
confidence: 99%
See 4 more Smart Citations
“…Fig.8 shows that lowering the pH raised the K" optimum of the 30-S-coupled EF-G GTPase reaction. This suggests [24] that negative charges, probably from ribosomal RNA, are exposed in the vicinity of the catalytic center, upon interaction between the ribosomal subunits.…”
Section: Modulation By P H Of Ef-g Gtpase Activitymentioning
confidence: 99%
“…Moreover, Douzou and Maurel [24] have shown that they partake in ionic regulation at concentrations far below the amounts required to obtain similar effects with monovalent cations. This led to the distinction between polyamines as 'internal modulators', and monovalent cations or pH as 'external modulators', [24].…”
Section: Influence Of Spermidine On Ef-g Gtpase Activity and Its Possmentioning
confidence: 99%
See 3 more Smart Citations